2018
DOI: 10.1037/spq0000213
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and academic outcomes associated with in-school suspension.

Abstract: The negative consequences associated with out-of-school suspension (OSS) are widely recognized, yet its commonly utilized counterpart, in-school suspension (ISS), has received little attention. This study examined school and student characteristics that predicted ISS and its links to academic outcomes, using the nationally representative High School Longitudinal Study of 2009. The sample included 11,860 public high school students, equating to a nationally representative sample of 2,993,918 students upon the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…Close to half of the students attend school in a suburban setting, whereas a third attend school in an urban setting. Almost 12% of students have received ISS at least once in the first semester of the school year, which is consistent with rates in other nationally representative samples (Cholewa et al, 2018). Over 40% have reported that they have misbehaved in some way in that same time frame.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Close to half of the students attend school in a suburban setting, whereas a third attend school in an urban setting. Almost 12% of students have received ISS at least once in the first semester of the school year, which is consistent with rates in other nationally representative samples (Cholewa et al, 2018). Over 40% have reported that they have misbehaved in some way in that same time frame.…”
Section: Resultssupporting
confidence: 87%
“…ISS is often seen as a less punitive type of exclusionary discipline; however, it is still associated with severe outcomes as well, including lower grade point average and higher risk of dropout (Cholewa, Hull, Babcock, & Smith, 2018). In the 2011 to 2012 school year, 3.5 million American students were given ISS, often under the complete discretion of an administrator, compared with 3.45 million students receiving out-of-school suspension (U.S.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Searching the Internet for racial slurs and other derogatory terms may be a proxy for racism at the macro level and linked with health outcomes and other indicators at the micro level (Chae et al, 2015, 2018). Internet‐based measures could also be used to determine racial disparities given that Black American children and adolescents are disciplined, suspended, and expelled at higher rates than their same‐gender counterparts of other ethnic‐racial groups in school settings (Cholewa, Hull, Babcock, & Smith, 2018). Among the questions that need to be addressed: Are Google searches of the n‐word linked to school districts that exhibit racial disparities in discipline, suspension, and expulsion of Black American youth?…”
Section: Research On Multiple Types Of Racismmentioning
confidence: 99%
“…In-school suspensions have been introduced in response to criticisms of out-of-school suspensions (Chobot & Garibaldi, 1982; Zimmerman & Archbold, 1979). However, in-school suspensions have hardly shown themselves to be a panacea: Like out-of-school suspensions, in-school suspensions are also associated with negative educational outcomes, including lower educational achievement (Noltemeyer, Ward, & Mcloughlin, 2015), lower grades, and higher dropout rates (Cholewa, Hull, Babcock, & Smith, 2017). In addition, given that interventions that allow at-risk youth to spend more time with other at-risk youth can exacerbate problematic behavior (Dodge, Dishion, & Lansford, 2006; McCord, 2003), in-school suspensions likely result in undesirable student development, especially when teachers view in-school suspensions as a “dumping ground” for students with uncontrollable behavior (Diem, 1988).…”
Section: Suspensions and Student Developmentmentioning
confidence: 99%